2021
DOI: 10.1038/s41598-021-01405-0
|View full text |Cite
|
Sign up to set email alerts
|

Developing an in-vivo physiological porcine model of inducing acute atraumatic compartment syndrome towards a non-invasive diagnosis using shear wave elastography

Abstract: Compartment syndrome (CS) is a pathological event caused by elevated intracompartmental pressure (ICP); however, changes from the onset of inducing atraumatic CS remained unclear. The study aimed to investigate the physiological changes in a newly developed in vivo porcine acute atraumatic CS model. CS was induced by ischemia–reperfusion injury in the left hind leg of fourteen pigs divided into an echogenicity group (EG) and a shear wave elastography group (SEG). Echogenicity was measured in EG, and shear elas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, the straps used in this research setup prevented the measurement of intramuscular pressure and muscle stiffness as shear elastic modulus, simultaneously. In our previous study, it was shown that muscle compartment syndrome increased intramuscular pressure and influenced muscle stiffness using shear-wave elastography [ 29 ]. Therefore, the change in the difference in derived muscle stiffness from the ACC data ( Fig 6A ) between the control and experimental legs indicates that mechanical changes associated with VC could occur.…”
Section: Discussionmentioning
confidence: 99%
“…However, the straps used in this research setup prevented the measurement of intramuscular pressure and muscle stiffness as shear elastic modulus, simultaneously. In our previous study, it was shown that muscle compartment syndrome increased intramuscular pressure and influenced muscle stiffness using shear-wave elastography [ 29 ]. Therefore, the change in the difference in derived muscle stiffness from the ACC data ( Fig 6A ) between the control and experimental legs indicates that mechanical changes associated with VC could occur.…”
Section: Discussionmentioning
confidence: 99%
“…Each pig was rested for 3 days in a comfortable cage with easy access to water except, for eight hours before the experiment. The experimental setup was designed based on previous our study [ 37 ]. The animal preparation was done similarly reported in our previous study [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The experimental setup was designed based on previous our study [ 37 ]. The animal preparation was done similarly reported in our previous study [ 37 ]. Briefly, sedation was done using the cervical intramuscular injection of Azaperone (5 mg/kg), Alfaxalone (4 mg/kg), Xylazine (2 mg/kg), and Atropine (0.05 mg/kg).…”
Section: Methodsmentioning
confidence: 99%